UMP students shine in Perodua Eco-Challenge - UMP, PNC
Universiti Malaysia Pahang (UMP) recorded another milestone when students from the university’s chapter of Society of Automotive Engineers (SAE) took second spot in the Perodua Eco-Challenge’s Manual Transmission (M/T) category, bringing home a cash prize of RM10,000.